From drugs to targets: Reverse engineering the virtual screening process on a proteomic scale - Schottlender, Gustavo; Prieto, Juan Manuel; Palumbo, Miranda Clara; Castello, Florencia A.; Serral, Federico; Sosa, Ezequiel J.; Turjanski, Adrián G.; Martì, Marcelo A.; Fernández Do Porto, Darío (Frontiers in Drug Discovery, 2022)
Phenotypic screening is a powerful technique that allowed the discovery of antimicrobials to fight infectious diseases considered deadly less than a century ago. In high throughput phenotypic screening assays, thousands of compounds are tested for their capacity to inhibit microbial growth in-vitro. After an active compound is found, identifying the molecular target is the next step. Knowing the specific target is key for understanding its mechanism of action, and essential for future drug development. Moreover, this knowledge allows drug developers to design new generations of drugs with increased efficacy and reduced side effects. However, target identification for a known active compound is usually a very difficult task. In the present work, we present a powerful reverse virtual screening strategy, that can help researchers working in the drug discovery field, to predict a set of putative targets for a compound known to exhibit antimicrobial effects. The strategy combines chemical similarity methods, with target prioritization based on essentiality data, and molecular-docking. Specific steps can be tailored according to the researchers' needs and pathogen’s available information. Our results show that the method is capable of retrieving potential targets for half of tested compounds. Moreover, if a target is retrieved, the actual true target is among the handful of retrieved proteins in at least 80% of the cases. We expect to integrate the presented strategy in the context of Target Pathogen database to make it available for the wide community of researchers working in antimicrobials discovery.